IMPLEMENTASI MISI PERGURUAN TINGGI DALAM PEMBERDAYAAN USAHA KECIL MELALUI PENDEKATAN INKUBATOR BISNIS - Hadiyati, Ernani (Journal of Innovation in Business and Economics, 2010)
This study is aimed to elaborate the importance of Business Incubator in a Higher Education Institution, as one of tools of Tri-Dharma Perguruan Tinggi missions. The unit executes entrepreneurship training and education for society, business research, dedication for society; by performing building management for small-medium enterprises, informal sectors, cooperative, and other business activities which touching all people in the grace-root. In the word, Incubator Business is the mission of the institution, especially dedication for society’s mission, in order to develop a strong ‘ekonomi kerakyatan’. It is important to socialize the urgency of the unit development in the higher education institution through seminar, training, presentation, and alliance programs among the institution.